Vascular Safe Zones for Facial Soft Tissue Filler Injections. Issue 2 (April 2022) - Cotofana, Sebastian; Lowrey, Nicola; Frank, Konstantin; Ziebart, Rachel; Guertler, Anne; Freytag, Lysander; Helm, Sabrina; Alfertshofer, Michael G.; Moellhoff, Nicholas
Abstract : The number of soft tissue filler injections performed by aesthetic injectors has continued to increase over the last few years. To provide a high standard of safety and achieve individualized, reproducible, and long-lasting outcomes, aesthetic injectors must have a solid foundation in anatomy, facial biomechanics, rheology, and injection biomechanics. Adverse events associated with soft tissue filler injections can be severe, especially if the aesthetic injector unintentionally injects the soft tissue filler into the patient's arterial vascular circulation and the administered product reaches the arterial bloodstream. Although the face has a rich arterial vascular supply that may seem overwhelmingly complex, it can be broken down systematically according to its internal and external vascular territories. To provide guidance for aesthetic practitioners performing minimally invasive facial injections for aesthetic purposes, this narrative article will discuss the course, depth, and branching pattern of the facial arteries based on the most frequently injected anatomical regions. In this article, we focus on vascular safe zones rather than danger zones .